Prevention of SIVmac251 reservoir seeding in rhesus monkeys by early antiretroviral therapy. Issue 1 (December 2018) - Whitney, James; Lim, So-Yon; Osuna, Christa; Kublin, Jessica; Chen, Elsa; Yoon, Gyeol; Liu, Po-Ting; Abbink, Peter; Borducci, Erica; Hill, Alison; Lewis, Mark; Geleziunas, Romas; et al.
Abstract The precise time when the viral reservoir is seeded during acute HIV-1 infection remains unclear. We previously demonstrated that the viral reservoir was seeded by day 3 following SIVmac251 infection in rhesus monkeys. Here we report the impact of initiating ART on day 0 (6 h), 1, 2, or 3 following intrarectal SIVmac251 infection in 20 rhesus monkeys (N = 5/group). After 6 months of daily suppressive ART, antiretroviral drugs were discontinued, and viral rebound was monitored. 0% (0 of 5), 20% (1 of 5), 60% (3 of 5), and 100% (5 of 5) of animals that initiated ART on days 0 (6 h), 1, 2, or 3, respectively, showed viral rebound following ART discontinuation and correlated with integrated viral DNA in lymph node CD4+ T cells. These data demonstrate that the viral reservoir is seeded within the first few days of infection and that early ART initiation limits the viral reservoir. The latent HIV-1 reservoir is the key obstacle for curing HIV-1 infection, but the timepoint at which the HIV-1 reservoir is established is currently unclear. Here, Whitney et al. show in non-human primates that the SIV reservoir in CD4+ T cells is seeded within the first 2 days after infection.